Electrochemical detection of poly(3-hydroxybutyrate) production from Burkholderia glumae MA13 using a molecularly imprinted polymer-reduced graphene oxide modified electrode - da Conceição, Emanuela [UNESP]; Buffon, Edervaldo [UNESP]; Beluomini, Maísa Azevedo [UNESP]; Falone, Max Fabrício [UNESP]; de Andrade, Fernanda Batista [UNESP]; Contiero, Jonas [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Springer Nature, 2024)
The development and application of an electrochemical sensor is reported for detection of poly(3-hydroxybutyrate) (P3HB) – a bioplastic derived from agro-industrial residues. To overcome the challenges of molecular imprinting of macromolecules such as P3HB, this study employed methanolysis reaction to break down the P3HB biopolymer chains into methyl 3-hydroxybutyrate (M3HB) monomers. Thereafter, M3HB were employed as the target molecules in the construction of molecularly imprinted sensors. The electrochemical device was then prepared by electropolymerizing a molecularly imprinted poly (indole-3-acetic acid) thin film on a glassy carbon electrode surface modified with reduced graphene oxide (GCE/rGO-MIP) in the presence of M3HB. Electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), scanning electron microscopy with field emission gun (SEM-FEG), Raman spectroscopy, attenuated total reflection Fourier-transform infrared (ATR-FTIR) and X-ray Photoelectron Spectroscopy (XPS) were employed to characterize the electrode surface. Under ideal conditions, the MIP sensor exhibited a wide linear working range of 0.1 – 10 nM and a detection limit of 0.3 pM (n = 3). The sensor showed good repeatability, selectivity, and stability over time. For the sensor application, the bioproduction of P3HB was carried out in a bioreactor containing the Burkholderia glumae MA13 strain and sugarcane byproducts as a supplementary carbon source. The analyses were validated through recovery assays, yielding recovery values between 102 and 104%. These results indicate that this MIP sensor can present advantages in the monitoring of P3HB during the bioconversion process. Graphical Abstract: (Figure presented.)
Keywords: Biomass; Bioplastics; Differential pulse voltammetry; Graphene; Methanolysis; Modified glassy carbon electrode; Molecularly imprinted sensor